(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the symbolical meaning of the terms moon and star in Ivan Franco’s poetry. By using the specific examples we have illustrated the functioning of these terms in various symbolical meanings, which proves the author’s deep erudition, his perfect poetical talent.